Isolation And Screening Of Fungi Producing Cellobiose Dehydrogenase: "Enzymes For Animal Feed Preparations Based On Enzymatic Process" - DESRIANI; WIWIT AMRINOLA; NENENG HASANAH; RIVAI; BAMBANG PRASETYA; PUSPITA LISDIYANTI (International Journal of Pharma and Bio Sciences, 2012)
Cellobiose dehydrogenase (CDH, EC 1.1.99.18) is an extracellular enzyme, potential used for animal feed preparation through fenton mechanism. Isolation and screening of fungi that produced CDH was investigated. Soil samples as the fungi source were obtained from several places in Indonesia such as in Aceh, North Sumatra, Central Java and West Java. YPD (yeast extract, peptone, dextrose) media was used for fungi isolation media. Screening of fungi producing CDH was divided in two stages.The first stage of screening was carried out by growing isolated fungi on CMC media. The fungi which form a clear zone after congo red coloration treatment was selected for the second stage. Screening of the second stage was done by checking and measuring the activity of CDH refer to Desriani et al., 2010. The results showed, among 25 isolated fungi obtained, 3 of them generated clear zone with their CDH activity were Coprinus sp. 0.79 U/ml; Sp2 code 0.36 U/ml; Sp.3 code 0.28 U/ml. The CDH activity of Mucor sp as the negative control was 0.004 U/ml. Of the 3 isolated fungi, Coprinus sp is promising to be applied in animal feed preparation based on enzymatic process.